Creativity A Force to Innovation - Jain, Pooja (IntechOpen, 2021)
Creativity and innovation go hand in hand. This book presents a plethora of creative interventions in education, culture, expressions, communications, and other areas. Each chapter brings forth a core idea well attested on the scales of creative interventions. It is a collaborative effort to bring forth multidisciplinary creativity in the ever-evolving world of design, communication, and possibilities. There is really no logical order to the book. You do not necessarily have to start at the beginning, just find a chapter that interests you and read. I hope that you find the book stimulating as well as informative.